Forty-five years of removal campaigns for feral ungulates reveal strategies for success and future directions - Nathan P. Snow; Keely J. Kohen; Ingrid A. Messer; Abigail Pagels; Seth M. Cook; Scott Beckerman; Travis Guerrant; Kurt C. VerCauteren; Kim M. Pepin (Biological Invasions, 2025)
Feral or invasive ungulates (hereafter: feral ungulates) exist worldwide, and their ability to thrive threatens biodiversity, degrades ecosystems, and causes damage to agriculture and properties. Strategies for removing feral ungulates from their introduced insular and mainland ranges have varied greatly, successes have been difficult, and the need is increasing. We reviewed published scientific literature on feral ungulate eradication and maximum control campaigns during 1978–2023 to identify practices that led to greater success. Of 54 campaigns, 32 (59%) reported success. Most campaigns focused on feral swine (61%; Sus scrofa ) or feral goats (24%; Capra hircus ). The average duration of a campaign was 61 months and cost an average of $1.9 m ($USD 2024) or $636/km 2 /month. The most important components for success included ensuring adequate funding was secured for the campaign ($0.5–1 million/km 2 is recommended) and population recovery or reinvasion were minimized. The frequency of campaigns has increased during the last 45 years; however, the areas worked (km 2 ), monthly durations, removal techniques used, funding, and ultimately the rates of success have not changed. A lack of increasing success for larger and more complex campaigns indicated that modernization of technologies for population control has been minimal, and larger breakthroughs are needed. Safe and effective toxicants and sterilants may provide those advances if developed. Lessons learned from campaigns indicate that pilot testing control methods prior to initiating full campaigns may help to alleviate uncertainties, produce more reliable plans, and help inform the biology of the animals being targeted for removal.

Locating and eliminating feral swine from a large area of fragmented mixed forest and agriculture habitats in north-central USA - Richard M. Engeman; Bradley E. Wilson; Scott F. Beckerman; Justin W. Fischer; Doug Dufford; James Bryan Cobban (Environmental Science and Pollution Research, 2019)

Tracking of Drug Release and Material Fate for Naturally Derived Omega-3 Fatty Acid Biomaterials - Keith M. Faucher; Natalie Artzi; Moshe Beck; Rita Beckerman; Geoff Moodie; Theresa Albergo; Suzanne Conroy; Alicia Dale; Scott Corbeil; Paul Martakos; Elazer R. Edelman (Annals of Biomedical Engineering, 2016)

Benefits to rare plants and highway safety from annual population reductions of a “native invader,” white-tailed deer, in a Chicago-area woodland - Richard M. Engeman; Travis Guerrant; Glen Dunn; Scott F. Beckerman; Chris Anchor (Environmental Science and Pollution Research, 2014)